Patterns of presentation and clinical toxicity after reported use of alpha methyltryptamine in the United Kingdom. A report from the UK National Poisons Information Service. (March 2014) - Kamour, A.; James, D.; Spears, R.; Cooper, G.; Lupton, D. J.; Eddleston, M.; Thompson, J. P.; Vale, A. J.; Thanacoody, H. K. R.; Hill, S. L.; Thomas, S. H. L.
Abstract Objective. To characterise the patterns of presentation, clinical effects and possible harms of acute toxicity following recreational use of alpha methyltryptamine (AMT) in the United Kingdom, as reported by health professionals to the National Poisons Information Service (NPIS) and to compare clinical effects with those reported after mephedrone use. Methods. NPIS telephone enquiries and TOXBASE® user sessions, the NPIS online information database, related to AMT were reviewed from March 2009 to September 2013. Telephone enquiry data were compared with those for mephedrone, the recreational substance most frequently reported to the NPIS, collected over the same period. Results. There were 63 telephone enquiries regarding AMT during the period of study, with no telephone enquiries in 2009 or 2010, 19 in 2011, 35 in 2012 and 9 in 2013 (up to September). Most patients were male (68%) with a median age of 20 years. The route of exposure was ingestion in 55, insufflation in 4 and unknown in 4 cases. Excluding those reporting co-exposures, clinical effects recorded more frequently in AMT (n = 55) compared with those of mephedrone (n = 488) users including acute mental health disturbances (66% vs. 32%; Odds Ratio [OR], 4.00; 95% Confidence Intervals [CI], 2.22–7.19), stimulant effects (66% vs. 40%; OR, 2.82; 95% CI 1.57–5.06) and seizures (14% vs. 2%; OR, 9.35; 95% CI 3.26–24.18). Conclusions. Although still infrequent, toxicity following reported exposure to AMT has been encountered in the United Kingdom since January 2011. Stimulant features, acute mental health disturbances and seizures are more frequently reported than in those presenting following reported use of mephedrone.